Base temperature for node emission and plastochron determination in tomato species and their hybrids - Zeist, André Ricardo; Resende, Juliano Tadeu Vilela de; Faria, Marcos Ventura; Gabriel, André; Silva, Israel Felipe Lustosa da; Lima Filho, Renato Barros de (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to estimate the base temperature for node emission and plastochron determination in wild species of tomato, in the Redenção cultivar, and in their respective interspecific F1 hybrids. The wild accessions Solanum pimpinellifolium AF 26970, Solanum galapagense LA-1401, Solanum peruvianum AF 19684, Solanum habrochaites var. hirsutum PI-127826, Solanum habrochaites var. glabratum PI-134417, and Solanum pennellii LA-716; the cultivar Redenção (Solanum lycopersicum); and their respective interspecific hybrids were evaluated, on the transplanting dates 12/22/2015, 2/12/2016, and 4/6/2016. The base temperature was estimated using the least mean squared error of the linear regression between the number of nodes and the accumulated thermal sum. The plastochron for the main stem and the first three lateral stems was estimated using the base temperature. The base temperature for node emission and plastochron determination varied from 4.5 to 14.8°C. The species S. habrochaites var. hirsutum accession PI-127826, S. habrochaites var. glabratum accession PI-134417, and their hybrids with the Redenção cultivar showed the lowest base temperatures and plastochron for the main stem, whereas the remaining wild species and interspecific hybrids had a base temperature near that of cultivated tomato. Wild species and interspecific hybrids of tomato show a great variation in base temperature for node emission and plastochron determination.